Differences in the sodium content of bread products in the USA and UK: implications for policy. Issue 3 (21st November 2017) - Coyne, Kasey J; Baldridge, Abigail S; Huffman, Mark D; Jenner, Katharine; Xavier, Dagan; Dunford, Elizabeth K
Abstract: Objective: Americans consume Na in excess of daily recommendations. Most dietary Na comes from packaged foods, and bread is a major contributor. In the UK, national Na reduction strategies contributed to lower Na levels in packaged foods and lower population Na intake. Similar initiatives are emerging in the USA and require surveillance to assess effectiveness. We aimed to examine Na levels in bread products in the USA and compare levels with similar UK products. Design: Na data for bread products were obtained from the US Label Insight Open Data Initiative ( n 4466) and the FoodSwitch UK database ( n 1651). Mean, median and range of Na content, and proportion of products meeting Na targets established by the National Salt Reduction Initiative (NSRI) and the UK Department of Health (DH) were calculated overall, by bread type and by country. Results: Mean (sd ) Na content in bread was 455 (170) mg/100 g in the USA and 406 (179) mg/100 g in the UK. In both countries, savoury bread had the highest mean Na (USA=584 mg/100 g, UK=543 mg/100 g) and fruit bread the lowest mean Na (USA=345 mg/100 g, UK=277 mg/100 g). Na content of US bread products was 12 % higher than in the UK, with 21 % of US bread products and 31 % of UK bread products meeting the NSRI and DH targets, respectively. Conclusions: US bread products have, on average, 12 % more Na than similar products in the UK. Variation in Na content within product categories, and between countries, suggests the feasibility of manufacturing products with lower Na to lower dietary Na intake.